Biodiversity researchers as a model for school students: An innovative approach to foster meaningful understanding? - Wiegelmann, Judith; Zabel, Jörg (Environmental Education Research, 2021)
The 2019 published report of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem (IPBES) reveals that the decline in species and habitats induced by human activities is continuing. School students still have difficulties to understand the meaning of biodiversity and the consequences of its loss. The underlying assumption of this study is that learners do not only need a scientific understanding of biodiversity in order to perceive it as personally meaningful. Rather, they should also have the opportunity to relate this complex topic to their individual nature experiences. This study pursues the idea that the biography of a biodiversity researcher can be used as a model for school students. A total of 18 German secondary school students at an average age of 15 years took part in this qualitative study. Data sampling included six group discussions with three participants each. We used an inductive as well as a deductive approach (category system) to analyze the data. Our results show that our study participants’ biographical nature experiences are appropriate to build bridges between biodiversity and themselves. Furthermore, we retraced meaningful understanding processes among the school students. These insights can inform biodiversity education.
Keywords: Biodiversity education; group discussions; school students; understanding processes